Detecção e distribuição genotípica do Papilomavírus humano (HPV) nos carcinomas anais - Libera, Larisse Silva Dalla (2016)
Anal cancer incidence is increasing significantly, especially when associated with the Human papillomavirus (HPV). The objective of this study was to evaluate the clinicopathological aspects of anal cancers and their association with HPV detection and genotypic distribution. It was a retrospective epidemiological study, with the use of the clinicopathological secondary data and molecular analyses of specimens of anal cancers embedded in paraffin blocks, diagnosed in a reference institution in the treatment of cancer at the Centro-Oeste region in a period of ten years (2000-2010). It was initially consulted a list of 140 cases of anal cancers but only 81 were included in the study. Molecular analysis included the amplification and detection of a viral genome fragment, by using PCR (polymerase chain reaction), and genotyping by reverse hybridization, using the commercial kit INNO LiPA. Data analysis was performed by descriptive statistics, univariate analysis and survival. According to the cases evaluated (n 81), 53.1% were more than 61 years of age, and the majority (63%) were females; 51.9% (n 42) presented squamous cells carcinoma (SCC). Lymph node metastases were described in 25.9%, distant metastases in 8.6% being the liver and the lung the most affected organs, the death was recorded in 45 cases (55.6%). HPV DNA was positive in 69% of cases. In the analysis by histologic type, 88.1% of squamous cell carcinomas (SCC), and 43.8% of adenocarcinomas was positive for viral DNA. The ECC was associated with HPV (p 0.0001) as well as females (p 0.01). Multiple infections were detected in 14.3% of the cases. The most prevalent genotypes were HPV16, HPV33 and HPV18. HPV 16 was found in 100% of multiple infections. After five years, overall survival was 44.3% for the group, the prognostic factors worse were female sex (p 0.008), squamous cell carcinoma (p 0.01) and the presence of distant metastasis (p 0. 01). Survival was not influenced by the presence of HPV (p 0.54). The aggressiveness of anal cancer described in this study reinforces the need of prevention strategies for this type of disease, including the HPV vaccine.